Institutional Preservation Work at a Family Business in Crisis: Micro-processes, Emotions, and Nonfamily Members. Issue 6 (June 2019) - Lingo, Elizabeth Long; Elmes, Michael B.
While research tends to focus on how family members respond to and manage crises arising in family businesses, nonfamily members play important roles as well. In this qualitative study, we demonstrate how nonfamily actors—employees, customers, and vendors—engage in institutional preservation work to save a family business. We develop a theoretical model of how a diffuse constellation of low-power individuals can come to identify and act as agents of institutional preservation and identify the three subprocesses comprising preservation work: intensifying and harnessing emotions, building collective identity, and articulating shared interests. This model offers insight into how nonfamily members can come to exert control over family businesses and contributes to emerging literature on the role of emotional escalation and social media in institutional and family business research.